2011
DOI: 10.1016/j.biomaterials.2011.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cell-derived cardiac tissue patch with advanced structure and function

Abstract: Recent advances in pluripotent stem cell research have provided investigators with potent sources of cardiogenic cells. However, tissue engineering methodologies to assemble cardiac progenitors into aligned, 3-dimensional (3D) myocardial tissues capable of physiologically relevant electrical conduction and force generation are lacking. In this study, we introduced 3D cell alignment cues in a fibrin-based hydrogel matrix to engineer highly functional cardiac tissues from genetically purified mouse embryonic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
195
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(205 citation statements)
references
References 64 publications
9
195
0
Order By: Relevance
“…Cardiomyocytes, similar to skeletal muscle cells, increase active force development in response to increased preload (Frank-Starling mechanism). Several studies have shown the same to be true in engineered cardiac constructs [ Table 1 and (4,26,50,94,108,110)] and reported increases between 1.9 -10-fold. The substantial variation is likely in part due to practical difficulties in defining baseline values for force development.…”
Section: Tissue Engineering To Model (Human) Heart Tissue Functionmentioning
confidence: 76%
See 1 more Smart Citation
“…Cardiomyocytes, similar to skeletal muscle cells, increase active force development in response to increased preload (Frank-Starling mechanism). Several studies have shown the same to be true in engineered cardiac constructs [ Table 1 and (4,26,50,94,108,110)] and reported increases between 1.9 -10-fold. The substantial variation is likely in part due to practical difficulties in defining baseline values for force development.…”
Section: Tissue Engineering To Model (Human) Heart Tissue Functionmentioning
confidence: 76%
“…The heart consists of fibroblasts, endothelial cells, and cardiomyocytes, raising the question as to whether a certain ratio of these three cell populations supports constitution of cardiac tissues in vitro. A few reports have addressed this question systematically and most support the hypothesis that endothelial cells and fibroblasts support tissue development (12,60,71,94), but one also reported inferior outcomes in the presence of fibroblasts (50), indicating that more work is required to answer this question.…”
Section: Tissue Engineering For Cardiac Repair: Different Approachesmentioning
confidence: 99%
“…Engineered muscle constructs were loaded into a custom-made force-measurement setup containing an optical force transducer and a linear actuator (ThorLabs), as previously described (25,26,42). Samples were stimulated (10 ms, 3 V/mm pulses) at different frequencies (1-40 Hz), and isometric passive and active (contractile) forces were measured at different muscle lengths.…”
Section: Methodsmentioning
confidence: 99%
“…74 Cardiac 3D constructs from chickens, rats, mice, and humans show a positive inotropic and chronotropic response to β-adrenergic stimulation, which is sensitive to the muscarinic agonist carbachol. 74 Furthermore, they increase force with ; in rat, 76 murine, 22 and mouse EHTs, 77 it was negative. Collectively, this demonstrates that 3D engineered tissues function qualitatively like native muscle.…”
mentioning
confidence: 95%